Problematika Pendidikan di Perbatasan: Studi Kasus Pendidikan Dasar bagi Anak Pekerja Migran Indonesia (PMI) di Negara Bahagian Sarawak, Malaysia - Handoyo, Budi Sulistya; Triarda, Reza (Jurnal Transformasi Global, 2020)
Education as one of the basic rights or fundamental rights that everyone must own has been discussed since 1948 in the Universal Declaration of Human Rights. Primary education becomes important later because education is a strategic aspect of human life.Â  Malaysia, as one of the destination countries of Indonesian migrant workers as a place to work. From the data of 2.7 million people spread throughout the territory of Malaysia. The problems that arise are not only in the administration of the workers but also the children they bring to work there. It becomes a dilemma because the government cannot go down directly because of obstacles such as national borders and the applicable rules. The Transnational Public-Private Partnership, which is then carried out between the two countries and a third party, private then, can fulfill that education. CLC or Community Learning Center is a manifestation of this form of public-private collaboration. In this case, the private sector's involvement is significant in fulfilling the education of Indonesian migrant worker children in the Sarawak region. To date, 62 CLCs provide access to education for 1,658 Indonesian children. With local teachers/tutors who are Indonesian citizens, the company recruits to teach with a minimum high school / vocational certificate. Until June 2019, there were 94 Pamong Teachers in the Sarawak CLC, and Bina Teachers were teachers sent by the Indonesian Government (Kemendikbud RI) to teach at the CLC. As of June 2019, there were 23 Bina Teachers in the Sarawak CLC.